PENGARUH VIDEO ADVERTISING DAN SOSIAL MEDIA KONTEN MELALUI BRAND AWARENESS TERHADAP MINAT BELI PADA APLIKASI GOFOOD DI KOTA MAKASSAR - Mashur Razak; Muhammad Hidayat; Muhammad Hdayatullah Rahman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
The purpose of this study is to analyze the direct and indirect effects of video advertising and social media content through brand awareness toward purchase interest in the GoFood application in Makassar City. In this study, the researchers used descriptive study with a quantitative approach. The population in this study were 95 users of the GoFood application in Makassar City, determining the sample based on the Hair formula where the sample size was 5-10 times the number of indicators. This study used 19 indicators at times 5 so that the number of samples becomes 95. The sampling technique used random sampling with a purposive sampling approach. The data analysis technique in this study was Partial Least Square using the Smart PLS application. The results of this study indicate that (1) Video advertising has an effect toward purchase intention (2) Social media content has no effect toward purchase intention (3) Video advertising through brand awareness has an effect toward purchase interest (4) Social media content through brand awareness has an effect toward purchase interest (5) Brand awareness affects purchase interest in the GoFood application in Makassar City.